2014
DOI: 10.3390/s141224212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reduced Terrestrial LiDAR Point Density on High-Resolution Grain Crop Surface Models in Precision Agriculture

Abstract: 3D geodata play an increasingly important role in precision agriculture, e.g., for modeling in-field variations of grain crop features such as height or biomass. A common data capturing method is LiDAR, which often requires expensive equipment and produces large datasets. This study contributes to the improvement of 3D geodata capturing efficiency by assessing the effect of reduced scanning resolution on crop surface models (CSMs). The analysis is based on high-end LiDAR point clouds of grain crop fields of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 47 publications
2
36
0
Order By: Relevance
“…The methodology of spatial plant height mapping can be scaled to field level, as long as the maximum range of the scanner is regarded and the point density is above the required minimum. As shown by Hä mmerle and Höfle [63], the coverage of the field and attained mean heights are influenced by the point density. The approach of pixel-wise calculating plant height from TLS-derived CSMs has already shown good results at the field level for monitoring a maize field, about 80 m by 160 m in size [74] and a sugar beet field, about 300 m by 500 m in size [43] captured from four and eight scan positions, respectively.…”
Section: Tls-derived Plant Heightmentioning
confidence: 99%
See 1 more Smart Citation
“…The methodology of spatial plant height mapping can be scaled to field level, as long as the maximum range of the scanner is regarded and the point density is above the required minimum. As shown by Hä mmerle and Höfle [63], the coverage of the field and attained mean heights are influenced by the point density. The approach of pixel-wise calculating plant height from TLS-derived CSMs has already shown good results at the field level for monitoring a maize field, about 80 m by 160 m in size [74] and a sugar beet field, about 300 m by 500 m in size [43] captured from four and eight scan positions, respectively.…”
Section: Tls-derived Plant Heightmentioning
confidence: 99%
“…Usually, the factors time and cost have a major influence on choosing a system. As shown by Hä mmerle and Höfle [63] the appropriate point density for generating a CSM varies depending on the application. In further studies, cost-efficient systems, such as the Velodyne HDL-64E [64], should be considered to investigate their potential for capturing crop surfaces in an adequate resolution.…”
Section: Tls-derived Plant Heightmentioning
confidence: 99%
“…It is possible to determine the ground surface shortly before transplanting or after harvesting the crop; however, in this study, the laser pulse easily reaches the rice canopy, and therefore we choose a new reference point at the top of the rice plant to determine H. The proposed method utilizes percentile analysis, which has been commonly used for analyzing plant heights obtained with a laser scanner. 25,26 Therefore, a procedure using percentile ranks and vertical distance was performed, whereby the closest percentiles to the top (p t ) and bottom (p b ) of the rice plant were determined. On the basis of this, the position of the top (D t ) and the bottom of the rice plant (D b ) were then located (Fig.…”
Section: Estimation Of Rice Plant Heightmentioning
confidence: 99%
“…Previous studies focused on the acquisition of plant height [25], post-harvest growth [26], leaf area index [27], crop density [28,29], nitrogen status [30], or the detection of individual plants [31,32]. Moreover, the potential of TLS for estimating the biomass of small-grain cereals was emphasized [33][34][35][36]. Regarding the accuracy, Lumme et al [33] found that estimated heights of cereal plants correlated with tape measurements.…”
Section: Introductionmentioning
confidence: 99%